TWO DECADES OF ISLAMIC LEADERSHIP AND ISLAMIC WORK ETHICS IMPLEMENTATION: BIBLIOMETRIC ANALYSIS - Suprayitno, Aryadimas; Susanto, Arva Athallah; Wahab, Abd (Sultan Syarif Kasim State Islamic University, Riau, 2025)
The present study explores the relationship between Islamic Leadership and Islamic Work Ethics, demonstrating how the two concepts are inextricably linked and both grounded in fundamental Islamic principles that advocate justice, integrity, and accountability. Islamic leadership, with its emphasis on the concept of adab (good character), serves as a framework for leaders to manage and apply ethical standards that the organisation seeks to uphold. This study aims to contribute to the existing body of research on Islamic Work Ethics by exploring it within the framework of Islamic Leadership. The analysis technique of this research is through bibliometric review related to Islamic Leadership and Islamic Work Ethics.The results of bibliometric visualisation show that Islamic Work Ethics (IWE) is a central concept that has a multidimensional influence on various aspects of management and organisations.Research over the past two decades indicates significant developments in the application of IWE, from normative approaches to practical dimensions, such as job satisfaction, knowledge sharing, and organisational performance. It is recommended that future research explore the application of IWE in a broader context, such as technology-based industries, in order to test the relevance of Islamic values in an increasingly globalised and dynamic work environment.